Building natural science learning through youth science camps - Piia Nuora (LUMAT, 2018)
This study focuses on a youth science camp for pupils in sixth to ninth grades that is organized annually by the University of Jyväskylä, Finland. The main idea of the science camp is to learn to do guided inquiry in nature. The study investigates the significance of science camp for encouraging young participants to learn science and how the camp supports their learning. The research method used was a survey. Altogether, 47 youth participated in the camp in 2012 and 2013. The results show that the participants wanted to learn more about science than secondary school could offer, and science camp had a positive impact on their interest in science. It was possible to introduce important concepts of chemistry and biology in a comprehensible manner through experimentation in an authentic context. The participants worked as researchers in a positive and non-formal learning environment and they received concrete experience with the various phases of scientific research.